The role of producers' associations in the valorisation of traditional products: an Italian North-West poultry and rabbit breeds consortium - Lazzaroni C.; Moriano G. (Mediterranean livestock production: uncertainties and opportunities, 2008)
The valorisation of traditional methods of production can be useful not only for the survival and recovery of local breeds but also for economic purposes and to guarantee higher incomes to breeders interested in a more sustainable livestock production. To achieve such objectives requires time and money to support the breeders, as well as an organized structure to market and promote the products. The amount of local breeds still reared in Italy is few in number: in the North West (Piemonte region) there are only two poultry breeds (the Piemontese Fawn Hen and the Saluzzo White Hen) and one rabbit breed (the Carmagnola Grey Rabbit). After years devoted to increasing the numbers of these animals as well as improving their productive performances, now a Producers' Association has been established to improve the marketing strategies for these three breeds.
2. Seminar of the Scientific-Professional Network on Mediterranean Livestock Farming (RME), 2006/05/18-20, Zaragoza, (Spain)